Análisis de las estrategias comunicacionales internas y externas de la empresa Mi Comisariato de la ciudad de Machala. - Blanca Morales, Alexandra Victoria (My University, 2020)
As a research project, it is to analyze the internal and external communication strategies of the Mi Comisariato Company in the city of Machala. Business communication is the essential part of every organization, which involves both the internal and external public, its good handling allows to obtain an advantage before its competitors, facilitating the achievement of its goals and adaptation to changes that occur in the environment. The strategic communication has as fundamental task to manage in an integral way the identity of the company, for the fulfillment of the objectives that the organizations wish to achieve. The present study seeks to identify the communication strategies of the company My Commissariat through qualitative and quantitative approach methods, with the purpose of proposing the correct strategies, for the same they were based on primary sources, for the collection of information they implemented tools such as interviews directed to the internal client and survey directed to the external client. The alternatives for the improvement of the internal and external communication of the Mi Comisariato Company is based on strategies that involve more members of the organization and the dissemination of the activities and services offered by the company to its external public.
Como proyecto de investigación es analizar las estrategias comunicacionales interna y externas de la empresa Mi Comisariato de la ciudad de Machala. La comunicación empresarial es la parte esencial de toda organización, la misma que involucra tanto al público interno como al externo, su buen manejo permite obtener una ventaja ante sus competidores, facilitando el logro de sus metas y adaptación ante cambios que se presentan en el entorno. La comunicación estratégica tiene como tarea fundamental gestionar de manera integral la identidad de la empresa, para el cumplimiento de los objetivos que las organizaciones desean alcanzar. El presente estudio busca identificar las estrategias comunicacionales de la empresa Mi Comisariato a través de métodos de enfoque cualitativo y cuantitativo, con la finalidad de proponer las estrategias correctas, para el mismo se basaron de fuentes primarias, para la recolección de la información se implementaron herramientas tales como entrevistas direccionadas al cliente interno y encuesta dirigida al cliente externo. Las alternativas para la mejora de la comunicación interna y externa de la empresa Mi Comisariato se basa a través de estrategias que involucran más a los miembros de la organización y en la difusión de las actividades y servicios que brinda la empresa a su público externo.
Keywords: COMUNICACIÓN EMPRESARIAL; CLIENTE INTERNO Y EXTERNO; COMUNICACIÓN ESTRATÉGICA; PROMOCIÓN